The Effectiveness of Logic Punishment to Reduce the Use of Abusive Language in Students - Meisya Rafacintya; Delfiana Irene Harya; Casman Casman; Uun Nurjanah (STIKES Hesti Wira Sriwijaya, 2025)
Introduction: The use of social media provides freedom of expression, both verbal and non-verbal, not rarely referring to the use of sarcastic sentences or rude words, especially among students, the majority of whom feel common to use rude language in everyday life. The study aims to test the effectiveness of logic punishment as an attempt to reduce the use of rude words and sarcastic sentences in students, with the solution given being logic punishment. Method: The research was launched in May 2024 using pre-experimental quantitative methods with two-day early observation techniques, application of logic punishment in 4 days, and transcription of two days post-logic punishing data obtained through observation and evaluation of results involving 20 students of Horizon University Indonesia, Karawang. Results: There is an effect of using Logic Punishment on decreasing rude word use in students. (p-value 0,001). Based on the results of research, the variations in abusive language spoken by Horizon University Indonesia students are classified into 4 types, namely conditions, objects, animals and body parts, with the average use of abusive language spoken by students being 91.6% in the high category and experiencing a decline to 8.4 % in the low category after the implementation of logic punishment. Conclusion: This study results that the application of logic punishment has a positive and significant influence on students' use of harsh words.